Left ventricular pseudoaneurysm due to patch dehiscence after ventricular septal rupture repair - Sanghvi, Sanjeev; Baroopal, Anil; Mathur, Rohit (International Journal of Research in Medical Sciences, 2016)
Ventricular septal rupture is a rare complication of acute myocardial infarction and has a high mortality. We present a case of 52-year-old male patient with left ventricular pseudoaneurysm due to patch dehiscence after surgical repair of post-myocardial infarction ventricular septal rupture.